The changing structure of red meat demand - Mintert, James (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Testing for a demand change was done using pork and beef demand models estimated over the 1950-1984 period. Results suggest that a structural change has taken place in both beef and pork demand. The beef demand change, however, appears to have been more severe than that noted for pork.
Keywords: Swine; Red Meat; Demand